HABITAT DAN PERILAKU BURUNG JULANG IRIAN (Rhyticeros plicatus) DI RESORT MASIHULAN SEKSI WILAYAH 1 TAMAN NASIONAL MANUSELA - Marni Yanti Sia; Cornelis K. Pattinasarany; Andri Tuhumury (Jurnal Hutan Tropis, 2020)
The purpose of this study was to determine the habitat and daily behavior of hornbills at Masihulan Resort, Manusela National Park. Study was conducted on March 2019. Ad libitum sampling method was used to observe the hornbills behavior, while combination of lines and line terraced was used to obtained vegetation data. Hornbills require a natural habitats that are not affected by human activity, but can also adapt to habitats that have been disturbed with low levels of interference. An important factor of habitat that affects the distribution and daily activities of hornbills are the presence of feeding trees and nesting trees. Diet sources of hornbills in both locations consist of five spesies of plants, namely Ficus benjamina, Octomeles sumatrana, Myristica lancifolia, Pometia pinatta, and Eugenia sp; they were more abundant on Ilie than Hua Hui Jalang. The behaviors that had been identified were feeding, calling, grooming, and beak rubbing behavior. Four behaviors were observed at Hua Hui Jalang, namely: feeding (8%), grooming (32%), beak rubbing (40%), and calling (20%); and threebehaviors were observed at Ilie, namely : feeding (29,17%), grooming (31.25%), and calling (39.58%).